London Leads the World: The Reinvention of London Fashion in the Aftermath of the Second World War. (15th April 2020) - Bide, Bethan
Abstract: In the face of widespread damage and disruptive government regulation, London fashion was presented with an opportunity to redefine and reinvent itself in the aftermath of the Second World War. This paper explores how the impacts of the conflict fused with broader changes in manufacturing and promotion to force structural changes in London's fashion industry in the late 1940s that resulted in the city developing a reputation as a center of design rather than production. Indications of this shift from production to design can be seen particularly clearly in the rising cultural capital of the London "brand" in mid-market ready-to-wear fashions for women. By focusing on this sector of the industry, this paper adds a new perspective to previous studies of postwar fashion by looking beyond the activities of a narrow band of high-end fashion houses. From the geographies of manufacturing to the symbolic use of London postcodes on garment labels, it compiles a comprehensive impression of the significant role played by London's mid-market fashion manufacturers in managing the fashionable reputation of the city at a time when its industry faced catastrophic decline and reflects on how this shaped London's development as a fashion city in subsequent decades.